Research review of the development of the explosive strength in basketball - Nikolic, D.; Kocic, M.; Ðošic, A.; Velickovic, M. (Sports Science and Health, 2017)
The ultimate performance in every sport, including basketball, is the result of a series of "bricks" stacked in the correct order. One of the dice is definitely an explosive power that is defined as the ability to manifest the maximum power for the maximum short time. The aim of this study was to gather previous studies that dealt with the development of the explosive strength in basketball. Total amount of 49 studies published between 2001 and 2016 was collected and subjected to analysis. The results showed that, for the development of the explosive strength, the plyometric training method is usually used, both with male and female basketball players. Also, the explosive force can be developed by using the complex training; the aquatic plyometric training; a combination of plyometric training and some other kind of training (dynamic stretching, strengthening without weights, sprinting, weight training, training of strength (no lifting)); specific sprint training; SAQ training; skipping rope; training consisting of strength training, different types of stamina and basketball technique; circuit breaker program; circuit training; combination of the sprint training exercises with weights; the plyometric training with additional load and the training of dynamic stretching.